SOCIAL AFFILIATIONOF STUDENT YOUNG PEOPLE AS A FACTOR OF ORGANIZATIONAL DEVELOPMENT OF HIGHER SCHOOL - Kuprii, Tetyana H. (Educological discourse, 2016)
The problem of афіліації is in-process examined as the social phenomenon of student group at higher school. Certainly importance of coexistence, recognize and to the collaboration in a student environment the result of which is a productive educational-educate, socially humanitarian and scientific process. The features of display of social necessities of personality are investigational in the basic spheres of its vital functions in the period of preparation at higher school with application of analysis of aspects of organizational culture. Intercommunication is analysed on the basis of results of empiric research between the motivational types of affiliationof student young people and them by organizational activity in higher educational establishment.